OPTIMALISASI KECERDASAN MAJEMUK GUNA PENINGKATAN PERTUMBUHAN EKONOMI - Indiati, Indiati (Universitas Muhammadiyah Magelang, 2009)
God's love for his subjects were not spelled out, in addition to everything in the world donated to humans, was also blessed with tremendous potential great, both the potential physical, psychological, and faith. With the potential that human beings are capable cultured, managing everything in the world, prosperity of the earth, rogue use everything becomes meaningful, and able to create peace among fellow human beings and the whole world. That happens when the human potential is well developed, but if not then it could happen that appears opposite. Optimization of multiple intelligences better intelligence-intellectual logic, language, movement, natuaral, spatial, spiritual, interpersonal, and intrapersonal, is one attempt to accelerate the establishment of peace, prosperity on earth, including the Earth Indonesian, particularly in efforts to increase economic growth.